Activating Rhetoric - boudjellal, elrabia (El Omda in Linguistics and Discourse Analysis, 2018)
In order for rhetoric to be aligned with modern literature and maintain it valid for use in creativity, composition, artistic and aesthetic evaluation, it is important to review its topics and procedures as well as following the updates of the latest rhetorical researches. In this article, we presented the reasons behind the repulsion to rhetoric to such point of accusing it with infertility, and therefore calling for its activation through new proposed topics and pedagogical alternatives in teaching it.